A method for reducing fuel consumption of urban scooters using vehicle design and traffic simulation. (April 2017) - Lin, Yu-An; Chen, Pao-An; Chan, Kuei-Yuan
Vehicular tailpipe emissions have one of the largest impacts on urban air quality. One way to reduce these hazardous emissions is to reduce the amount of fuel consumed by on-road vehicles. In this research, we consider both vehicle design and driver behavior as crucial elements in evaluating the environmental impact of two-wheel vehicles. Any redesign of vehicle specifications, results in different driving patterns that need to be re-evaluated in a realistic environment with traffic simulation. Therefore we developed traffic simulations with mixed fleets to model scooter/driver behaviors to reflect urban driving scenarios. Based on the results, a 31-variable continuous variable transmission (CVT) design and a 14-parameter cellular automata traffic model are integrated. Simultaneous redesign of CVT with traffic simulation can reduce the fuel consumption by 16.2% in our case study. This promising outcome demonstrates the need for multi-discipline integration of real-world traffic impact assessments and improvements.